Agronomy program in cassava - Thompson, RL (International Center for Tropical Agriculture, 1972)
The objectives of the agronomy program at CIAT are to increase production/ unit cost, increase and stabilize the supply of cassava available for the market, and reduce consumer prices. Three projects development of standards for efficient exptl procedures, international and national cooperative work, cassava cropping systems are outlined. (CIAT)